Insights into the diversity and survival strategies of soil bacterial isolates from the Atacama Desert - Reverdy, Alicyn; Hathaway, Daniel; Jha, Jessica; Michaels, Gabriel; Sullivan, Jeffrey; McAdoo, Daniela Diaz; Riquelme, Carlos; Chai, Yunrong; Godoy-Carter, Veronica (Frontiers in Microbiology, 2024)
The Atacama Desert, the driest, with the highest radiation, and one of the most ancient deserts in the world, is a hostile environment for life. We have a collection of 74 unique bacterial isolates after cultivation and confirmation by 16S rRNA gene sequencing. Pigmentation, biofilm formation, antimicrobial production against Escherichia coli MG1655 and Staphylococcus aureus HG003, and antibiotic resistance were assessed on these isolates. We found that approximately a third of the colonies produced pigments, 80% of isolates formed biofilms, many isolates produce growth inhibiting activities against E. coli and/or S. aureus, and many were resistant to antibiotics.The functional characterization of these isolates gives us insight into the adaptive bacterial strategies in harsh environments and enables us to learn about their possible use in agriculture, healthcare, or biotechnology.